Burden of cytomegalovirus reactivation post kidney transplant with antithymocyte globulin use in Thailand: A retrospective cohort study [version 1; referees: 2 approved] - Maria N. Chitasombat (2019)
© 2018 Chitasombat MN and Watcharananan SP. Background: Cytomegalovirus (CMV) is an important cause of infectious complications after kidney transplantation (KT), especially among patients receiving antithymocyte globulin (ATG). CMV infection can result in organ dysfunction and indirect effects such as graft rejection, graft failure, and opportunistic infections. Prevention of CMV reactivation includes pre-emptive or prophylactic approaches. Access to valganciclovir prophylaxis is limited by high cost. Our objective is to determine the burden and cost of treatment for CMV reactivation/disease among KT recipients who received ATG in Thailand since its first use in our center. Methods: We conducted a single-center retrospective cohort study of KT patients who received ATG during 2010-2013. We reviewed patients’ characteristics, type of CMV prophylaxis, incidence of CMV reactivation, and outcome (co-infections, graft function and death). We compared the treatment cost between patients with and without CMV reactivation. Results: Thirty patients included in the study had CMV serostatus D+/R+. Twenty-nine patients received intravenous ganciclovir early after KT as inpatients. Only three received outpatient valganciclovir prophylaxis. Incidence of CMV reactivation was 43%, with a median onset of 91 (range 23-1007) days after KT. Three patients had CMV end-organ disease; enterocolitis or retinitis. Infectious complication rate among ATG-treated KT patients was up to 83%, with a trend toward a higher rate among those with CMV reactivation (P = 0.087). Patients with CMV reactivation/disease required longer duration of hospitalization (P = 0.018). The rate of graft loss was 17%. The survival rate was 97%. The cost of treatment among patients with CMV reactivation was significantly higher for both inpatient setting (P = 0.021) and total cost (P = 0.035) than in those without CMV reactivation. Conclusions: Burden of infectious complications among ATG-treated KT patients was high. CMV reactivation is common and associated with longer duration of hospitalization and higher cost.